Investigating Transparent Radiative Film for Greenhouse Cooling - Wang Chenxi; Deng Fangfang; Zou Hao; Yang Ronggui; Wang Ruzhu (Zhileng xuebao)
To alleviate the problem of crop yield reduction and extinction arising from high temperatures in summer greenhouses, a radiative cooling film for greenhouses operated in summer was investigated. The sky radiative cooling effect of a film can be strengthened by integrating a transparent radiation layer with conventional near-infrared reflective materials. The optical properties of films at different wavelengths were determined experimentally, revealing a photosynthetically effective transmissivity of 65.9%, a near-infrared transmissivity of 20.9%, and a mid-infrared reflectivity of 88.1%. A greenhouse environment model was used to compare the greenhouse temperature and energy consumption for cooling with different covering materials. The simulation results showed that the radiative film can reduce the internal temperature of a closed greenhouse in Shanghai by 11.4 ℃, and the cooling contributions of the selective near-infrared reflector and the transparent radiative layer were 6.8 ℃ and 4.6 ℃, respectively. Using this film, the energy consumption of heat pumps in an active-cooling greenhouse can be reduced by 26.9%. This film offers a promising solution for achieving energy-efficient and high-yield agriculture during the hot summer.